Ischemic optic neuropathies - Hayreh, Sohan Singh (Springer, 2011)
Ischemic optic neuropathy, often referred to as a stroke of the optic nerve, is one of the major causes of visual impairment or loss of vision. Yet it is a highly controversial and confusing subject because of the general lack of in-depth scientific understanding of the subject. In this book the leading authority in the field describes in detail the current knowledge about the different forms of the often devastating disease. Insights into the underlying pathogenesis and peculiar clinical features are given, leading the reader to the most appropriate way of management. This information will help any physician dealing with patients who suffer from sudden loss of vision.